Hubungan Pelayanan Kesehatan Gigi dan Mulut terhadap Kepuasan Pasien di Puskesmas Mataoleo Kabupaten Bombana - Adriatman Rasak; Nur Awalia Putri Zainal; Inang Salfina (Universitas Ngudi Waluyo, 2024)
Dental and oral health services include dental medical services by dentists, dental and oral health care services bydental nurses and supporting care services by technicians. Dental and oral health care services are carried out in a comprehensive manner to individuals, families and communities that have a scope that focuses on basic promotive, preventive, and curative. Research Objectives namely knowing the relationship of dental and oral health services to patient satisfaction at the Mataoleo Health Center, Bombana Regency.This research method used is descriptive which aims to determine the relationship between dental and oral health services at the Mataoleo Public Health Center, Bombana District. Accidental sampling technique with a total population of 30 samples. The results showa that of the 30 samples, seen from the dimensions of Physical Evidence (Tangible) in general in the Yes category there are as many as 27 people (90%), from the Reliability dimension in general in the Yes category there are as many as 28 people (93%), from the dimensions Assurance in general is in the Yes category, namely 26 people (86,6%), from the Responsiveness dimension in general in the Yes category, namely 27 people (90%), and from the Empathy dimension in general the category Yes, as many as 25 people (83,3%). In conclusion, based on the results of the study it can be concluded that there is a relationship between dental and oral health services on patient satisfaction at the Mataoleo Health Center, Bombana Regency. ABSTRAK Pelayanan Kesehatan gigi dan mulut mencakup pelayanan medis gigi oleh dokter gigi, pelayanan asuhan kesehatan gigi dan mulut oleh perawat gigi dan pelayanan asuhan supporting oleh tekhisi. Pelayanan asuhan kesehatan gigi dan mulut di lakukan secara komprehensif kepada individu, keluarga dan masyarakat yang mempuyai ruang lingkup berfokuskan pada promotif, preventif, dan kuratif dasar. Metode Penelitian yang digunakan Deskriptif yang bertujuan untuk mengetahui hubungan pelayanan kesehatan gigi dan mulut di puskesmas mataoleo kabupaten bombana. Tehnik pengambilan sampel accidental sampling dengan jumlah populasi sebanyak 30 sampel. Hasil Penelitian menunjukkan bahwa dari 30 sampel, dilihat dari dimensi Bukti Fisik (Tangible) secara umum pada kategori Ya yaitu sebesar (90%), dari dimensi Kehandalan (Reliability) secara umum pada kategori Ya yaitu sebesar (93%), dari dimensi Jaminan (Assurance) secara umum pada kategori Ya yaitu sebanyak 26 orang (86%), dari dimensi Ketanggapan (Responsiveness) secara umum pada kategori Ya yaitu sebesar (90%), dan dari dimensi Empati (Emphaty) secara umum kategori Ya yaitu sebesar (83%). berdasarkan hasil penelitian ini bahwa ada hubungan pelayanan kesehatan gigi dan mulut terhadap kepuasan pasien untuk menjadi standar pelayanan Kesehatan dalam hal kepuasan pasien di puskesmas.